Grievous Temporal and Occipital Injury Caused by a Bear Attack - Sampath Chandra Prasad; Nikhil Dinaker Thada; Pallavi Rao; Smitha Rani Thada; Kishore Chandra Prasad (Case Reports in Otolaryngology)
Bear attacks are reported from nearly every part of the world. The chance of a human encountering a bear increases as the remote bear territory diminishes. The sloth bear is one of the three species of bears found in India, which inhabits the forests of India and its neighboring countries. Here we describe a teenager who came to us with a critical injury involving the face, temporal and occipital bones inflicted by a sloth bear attack. He underwent a temporal exploration, facial nerve decompression, pinna reconstruction, and occipital bone repair to save him from fatality.